The Routledge Handbook of Conference Interpreting. - Albl-Mikasa, Michaela; Tiselius, Elisabet (Oxford : Taylor & Francis Group, 2021)
Providing comprehensive coverage of both current research and practice in conference interpreting, the Handbook covers both core areas and cutting-edge developments. With an introduction by the editors, this is essential reading for all researchers, ​trainers, students and professionals of Conference Interpreting.
Conclusion.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Congresses and conventions-Translating services; Translating and interpreting; Electronic books